Promosi terhadap Keputusan Pembelian Produk Meubel CV. Defmel Leilem - Harapanku, Indah Wahyuni; Manoppo, Wilfried S.; Rogahang, Joula J. (Productivity, 2020)
This study aims to determine the effect of promotion (X) on purchasing decisions (Y) at CV. Defmel Leilem. This approach uses a quantitative approach, with a sample of 30 respondents using a Likert scale. The data collection technique in this research is by using online questionnaires. The analysis technique used in this research is simple linear analysis. Data that has met the analytical technique is processed using the SPSS (Statistical Package for social sciences) program tools. The results of this research indicate that promotion has a positive and significant effect on purchasing decisions.